Antioxidant and Histopathological Effects of Paraquat and Fluroxypyr Herbicides on the Apple Snail Pomacea canaliculata (Lamarck, 1822) - Alejandra D. Campoy-Diaz; Israel A. Vega; Maximiliano Giraud-Billoud (Stresses)
Argentina is among the top consumers of herbicides, yet studies on their environmental and health impact remain scarce. This work aimed to evaluate the effects of herbicide exposure on Pomacea canaliculata as potential biomarkers of contamination. Specifically, we investigated whether paraquat (Pq) and fluroxypyr (Fx) alter enzymatic antioxidant defenses in tissues following acute exposure and induce histological modifications in the digestive gland (DG), particularly in symbiotic corpuscles, after chronic exposure. The nominal no-observed-effect concentration on lethality (NOECL) values were 3.62 µg/g dry mass (DM) for Pq and 10.42 µg/g DM for Fx. After acute exposure, superoxide dismutase activity decreased in the DG but increased in the kidney for both herbicides. Catalase activity decreased in the gills but increased in the kidneys of exposed snails, while glutathione-S-transferase activity increased in the DG and kidney after Pq exposure. Following chronic exposure (Pq: 1.45 µg/g DM; Fx: 6.94 µg/g DM), epithelial thickening and vacuolization were observed in Fx-exposed snails. Morphometric analysis of the DG showed that Pq reduced the epithelial occupancy of the symbiont’s vegetative form while increasing its cystic form. These findings indicate that both herbicides impact antioxidant defenses, DG function and host–symbiont interactions, reinforcing the suitability of P. canaliculata as bioindicator organisms.